Insights from experiences comanaging woody invasive alien plants in Argentina - Powell, Priscila Ana (2023)
The complexities of invasive alien species (IAS) management call for a close collaboration among stakeholders to codevelop and comanage actions to deliver effective solutions. To achieve this vision, iterative codesign and co-implementation of solutions is imperative.Based on a rapid Strengths, Weaknesses, Opportunities and Threats analysis (SWOT), we synthesised the positive and negative aspects of comanagement experiences for woody IAS management in Argentina. We included four case studies in protected areas: (i) Ligustrum lucidum in a periurban mountain forest; (ii) Rubus asp ulmifolius in a subtropical forest; (iii) Acacia melanoxylon in a temperate grassland; and (iv) Hedera helix in a temperate forest.Universities, research institutes and protected areas led these management projects under varying economic, social and ecological objectives, and constrained by the availability of resources. However, these heterogeneous realities did not translate into significant differences in our comanagement experiences.We identified personal motivations and pre-existing funding for IAS management as key strengths for management actions. A relevant weakness was the ongoing undervaluation of applied research and stakeholder engagement in the Argentinian scientific system, resulting in a scarcity of research to inform management actions and a low interest in codesigning activities. Threats were related to the paucity of awareness and information on IAS management, and the lack of long-term funding. Nevertheless, recent national-level policies, such as the National Strategy for Exotic Invasive Species, together with the Forest Law for managing native forests and the mandate for the National Parks Administration to manage IAS, provide a unique opportunity to foster comanagement activities.We recommend the development and promotion of spaces to share experiences and establish conversations among stakeholders. This should be complemented by a better alignment of disparate public policies driving IAS management in Argentina, and increased financial assistance to support local initiatives and reduce uncertainty in long-term funding.